2010
DOI: 10.1111/j.1744-313x.2009.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Killer cell immunoglobulin‐like receptor gene diversity in a Caucasian population of Southern Brazil

Abstract: Killer immunoglobulin-like receptors (KIR) regulate the activity of natural killer and T cells through an interaction with specific human leucocyte antigen (HLA) class I molecules on target cells. Diversity in KIR gene content, KIR allelic and haplotype polymorphism has been observed between different ethnic groups. However, most population studies on KIR variability have focused on Europe and Asia, while Americas, Oceania and Africa remain poorly studied. The aim of this study was to analyse the variability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
5
5
0
Order By: Relevance
“…In the present study, we examined the distribution of HLA-B, HLA-C, and KIR genes in TB and/or HIVinfected patients and investigated the putative role of these genes in the occurrence of TB/HIV-IRIS. The individuals included in the present study had their HLA-B, HLA-C, and KIR genes determined, and the frequency data observed corroborated what has been described for the HIV-1-infected population [12,69] and the general Brazilian population [70][71][72][73][74][75]. HLA-B*08 and female gender were associated with protection against TB onset in the studied population.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, we examined the distribution of HLA-B, HLA-C, and KIR genes in TB and/or HIVinfected patients and investigated the putative role of these genes in the occurrence of TB/HIV-IRIS. The individuals included in the present study had their HLA-B, HLA-C, and KIR genes determined, and the frequency data observed corroborated what has been described for the HIV-1-infected population [12,69] and the general Brazilian population [70][71][72][73][74][75]. HLA-B*08 and female gender were associated with protection against TB onset in the studied population.…”
Section: Discussionsupporting
confidence: 87%
“…Molecular technique defining the KIR gene content of individuals, mainly based on PCR‐SSP, was well established. The distributions of KIR2DS4 gene in the patients with syphilis and healthy controls were 95.26% and 97.40%, respectively, which were similar with the previous report (90–100%) (Jobim et al. , 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Sixteen KIR genes were detected in 152 Drung individuals by sequence-specific PCR. As previously noted, genes encoding activating KIR are more variably distributed in comparison to genes encoding inhibitory KIR (14)(15)(16)(17)(18)(19). Indeed, the frequencies for genes encoding inhibitory KIR were generally higher than those for genes encoding activating KIR, with the exception of KIR2DL2.…”
Section: Discussionmentioning
confidence: 62%
“…In comparison to other populations, KIR genes are characteristically distributed in the Drung population because of polygamy and strong geographic and racial segregation. Indeed, as KIR genotypes are widely variable and polymorphic , analysis of KIR genes enables racial and ethnic tracing and assessment of the genetic relationship among geographically distinct populations . Although the distribution of KIR genes may reflect founder effects, and may suggest that the Drung probably descended from very few ancestors, ancestral origins remain uncertain.…”
Section: Discussionmentioning
confidence: 99%